Self-Expanding Metal Stenting for Palliation of Patients with Malignant Colonic Obstruction: Effectiveness and Efficacy on 255 Patients with 12-Month's Follow-up - Søren Meisner; Ferran González-Huix; Jo G. Vandervoort; Alessandro Repici; Dimitrios Xinopoulos; Karl E. Grund; Paul Goldberg; The WallFlex Colonic Registry Group (Gastroenterology Research and Practice)
Background. Self-expanding metal stents can alleviate malignant colonic obstruction in incurable patients and avoid palliative stoma surgery. Objective. Evaluate stent effectiveness and safety on palliation of patients with malignant colorectal strictures. Design. Two prospective, one Spanish and one global, multicenter studies. Settings. 39 centers (22 academic, 17 community hospitals) from 13 countries. Patients. A total of 257 patients were enrolled, and 255 patients were treated with a WallFlex uncovered enteral colonic stent. Follow-up was up to 12 months or until death or retreatment. Interventions(s). Self-expanding metal stent placement. Main Outcome Measures. Procedural success, clinical success, and safety. Results. Procedural success was 98.4% (251). Clinical success rates were 87.8% at 30 days, 89.7% at 3 months, 92.8% at 6 months, and 96% at 12 months. Overall perforation rate was 5.1%. Overall migration rate was 5.5%. Overall death rate during follow-up was 48.6% (124), with 67.7% of deaths related to the patient’s colorectal cancer, unrelated in 32.3%. Only 2 deaths were related to the stent or procedure. Limitations. No control group. Conclusions. The primary palliative option for patients with malignant colonic obstruction should be self-expanding metal stent placement due to high rates of technical success and efficacy in symptom palliation and few complications.